THE CONCEPT OF COMMUNITY ECONOMIC DEVELOPMENT IN ISLAMIC PERSPECTIVE - Asse, Ambo (Jurnal Iqtisaduna, 2019)
The concept of Islam relies on the source of his teachings, so what must be revealed in this study is how the Qur’an and the hadith of the Prophet speak about the economic development of the people, so that the concept of economic development can be formulated according to Islamic teachings. The concept of economic development of the ummah, refers to two sources of Islamic teachings, namely: al-Qur’a>n and the Hadith of the Holy Prophet, which gave birth to the principles and values of Islamic economics which were formulated through studies conducted on the two sources of Islamic teachings which were confronted with problems faced by the community or people that produce formulations that need to be developed as a concept that can realize the welfare of the community and people.